Endogenous Synthesis of Collagen and its Relation to Aging: A Systematic Review / Síntese Endógena do Colágeno e sua Relação com o Envelhecimento: Uma Revisão Sistemática - Feitosa, Pedro Walisson Gomes Feitosa Gomes; Moreira, Jorge Lucas de Sousa; Silva, Lucas Lima da; Oliveira, Bruno Farias; da Silva, José Arinelson; Pinto, Sandy Soares Alves; Costa, Lívia Luiza Ferreira da; Pinheiro, Sally de França Lacerda (ID on line. Revista de psicologia, 2022)
Abstract:The aim of the study was to carry out a systematic review of the literature on the interrelation between the production of endogenous collagen and the mechanisms of human aging. The methods involved Systematic search on the electronic database PubMed and Scopus in order to select published articles on the endogenous synthesis of collagen and the molecular cascades responsible for aging, following the items of the Guidelines for Systematic Reviews and Meta-analysis (PRISMA). As for the results, 885 articles were identified in the searched databases (858 in PUBMED and 27 in SCOPUS). After exclusion by abstract and title, 62 articles were selected for analysis of the full text. At the end, 13 articles were chosen as relevant to compose the qualitative synthesis. The articles pointed out that collagen synthesis occurs in processes of regeneration and formation of embryonic tissue. Regarding the relationship between such production and aging, advancing age reduces the mechanical strength of fibroblasts due to the accumulation of fragments of collagen fibers in the intercellular spaces, as well as being associated with alterations in the proportions of type 1 and type 3 collagen levels. Collagen synthesis may still be susceptible to interference of environmental and genetic factors, such as nutrition, hormone levels, UV radiation and mutations. Finally, hydrolyzed collagen (HC) supplementation was associated mainly with maintaining skin health. Conclusions are that the synthesis and molecular levels of collagen are modified due to aging. In this context, environmental and genetic factors are also active in modifying these levels and production. To mitigate some effects of the skin aging process, hydrolyzed collagen supplementation is being indicated as effective. Keywords: human aging, collagen; endogenous synthesis. Resumo: O objetivo do estudo foi realizar uma revisão sistemática da literatura sobre a inter-relação entre a produção de colágeno endógeno e os mecanismos do envelhecimento humano. Os métodos envolveram busca sistemática na base de dados eletrônica PubMed e Scopus para selecionar artigos publicados sobre a síntese endógena de colágeno e as cascatas moleculares responsáveis pelo envelhecimento, seguindo os itens do Guidelines for Systematic Reviews and Meta-analysis (PRISMA). Quanto aos resultados, foram identificados 885 artigos nas bases de dados pesquisadas (858 na PUBMED e 27 na SCOPUS). Após exclusão por resumo e título, 62 artigos foram selecionados para análise do texto completo. Ao final, 13 artigos foram escolhidos como relevantes para compor a síntese qualitativa. Os artigos apontaram que a síntese de colágeno ocorre em processos de regeneração e formação do tecido embrionário. Quanto à relação entre tal produção e o envelhecimento, o avanço da idade reduz a resistência mecânica dos fibroblastos devido ao acúmulo de fragmentos de fibras colágenas nos espaços intercelulares, além de estar associado a alterações nas proporções dos níveis de colágeno tipo 1 e tipo 3. A síntese de colágeno ainda pode ser suscetível à interferência de fatores ambientais e genéticos, como nutrição, níveis hormonais, radiação UV e mutações. Por fim, a suplementação de colágeno hidrolisado (HC) foi associada principalmente à manutenção da saúde da pele. As conclusões são que a síntese e os níveis moleculares de colágeno são modificados devido ao envelhecimento. Nesse contexto, fatores ambientais e genéticos também atuam na modificação desses níveis e produção. Para mitigar alguns efeitos do processo de envelhecimento da pele, a suplementação de colágeno hidrolisado está sendo indicada como eficaz. Palavras-chave: envelhecimento humano, colágeno; síntese endógena.